The Pangenome Diversity, Dynamics and Evolution of Genomes - Tettelin, Hervé; Medini, Duccio (Springer International Publishing : Imprint: Springer, 2020)
This open access book offers the first comprehensive account of the pan-genome concept and its manifold implications. The realization that the genetic repertoire of a biological species always encompasses more than the genome of each individual is one of the earliest examples of big data in biology that opened biology to the unbounded. The study of genetic variation observed within a species challenges existing views and has profound consequences for our understanding of the fundamental mechanisms underpinning bacterial biology and evolution. The underlying rationale extends well beyond the initial prokaryotic focus to all kingdoms of life and evolves into similar concepts for metagenomes, phenomes and epigenomes. The book's respective chapters address a range of topics, from the serendipitous emergence of the pan-genome concept and its impacts on the fields of microbiology, vaccinology and antimicrobial resistance, to the study of microbial communities, bioinformatic applications and mathematical models that tie in with complex systems and economic theory. Given its scope, the book will appeal to a broad readership interested in population dynamics, evolutionary biology and genomics.